Carbonized cotton textile with hierarchical structure for superhydrophobicity and efficient electromagnetic interference shielding. (October 2021) - Jia, Li-Chuan; Nie, Run-Pan; Xu, Ling; Yan, Ding-Xiang; Lei, Jun; Li, Zhong-Ming
Abstract: Endowing electromagnetic interference (EMI) shielding materials with superhydrophobicity is regarded as an effective method to guarantee their service reliability under harsh environments. However, it is still a great challenge to integrate superhydrophobicity on EMI shielding materials due to the requirement for complex structural design. Herein, an superhydrophobic EMI shielding textile was facilely fabricated by carbonizing cotton textile and regulating the surface structure with nano-sized carbon black (CB) and low-surface energy polydimethylsiloxane (PDMS). The composite textile exhibited a superior EMI shielding effectiveness (42.9 dB), a large water contact angle (157.8°), and a low sliding angle (6.9°). It also showed strong resistance to physical deformations and chemical environments. These attractive features were attributed to the joint action of highly conductive carbonized textile, CB coating with nanoscale roughness, and PDMS protective layer. This work provides novel ideas for designing superhydrophobic EMI shielding materials for applications in electronic equipment under harsh environment.